A Prototype System for Selective Dissemination of Broadcast News in European Portuguese. (21st June 2007) - Amaral Amaral, R. R.; Meinedo Meinedo, H. H.; Caseiro Caseiro, D. D.; Trancoso Trancoso, I. I.; Neto Neto, J. J.
Abstract : This paper describes ongoing work on selective dissemination of broadcast news. Our pipeline system includes several modules: audio preprocessing, speech recognition, and topic segmentation and indexation. The main goal of this work is to study the impact of earlier errors in the last modules. The impact of audio preprocessing errors is quite small on the speech recognition module, but quite significant in terms of topic segmentation. On the other hand, the impact of speech recognition errors on the topic segmentation and indexation modules is almost negligible. The diagnostic of the errors in these modules is a very important step for the improvement of the prototype of a media watch system described in this paper.